PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN LEMBAGA SOSIAL YAYASAN INSPIRASI ANAK BANGSA - Rizal Rahmawan; Choiriawati Choiriawato; Syaifuddin Syaifuddin (Bajang Institute, 2023)
Good work environment (good facilities and infrastructure) or bad (less spacious workspace, uncomfortable waiting room for customers because it can disrupt concentration in an organization). The comfort of the employee's work environment can trigger employees to work better so that employee performance can be achieved optimally. (2) The influence of the work environment on employee performance at the Inspirasi Anak Bangsa Foundation Social Institution. The work environment can be interpreted as the entire tooling faced, the surrounding environment in which a person works, the method of work, as the influence of his work both as individuals and as a group. The hypothesis in this study